Evaluation of stability and capsular bag opacification of a new foldable adjustable intraocular lens. (13th May 2015) - MacLean, Kyle D; Werner, Liliana; Kramer, Gregory D; Farukhi, M Aabid; Gardiner, Gareth L; Kahook, Malik Y; Mamalis, Nick
Abstract Background Incorrect lens power remains one of the most common reasons for intraocular lens explantation/exchange. We evaluated stability and effect on capsular bag opacification of a new foldable modular lens system, with a base component and an optic component in rabbit eyes. Methods Bilateral phacoemulsification was performed on six rabbits; one eye received the test lens (Harmoni Modular Lens, ClarVista Medical), whereas the other received a single‐piece hydrophobic acrylic control lens (SA60AT, Alcon). Slit‐lamp examinations were performed at postoperative weeks 1, 2, 3, 4 and 6. All rabbits were sacrificed at week 6. After enucleation, the eyes were examined grossly from the Miyake–Apple view. Following, all globes were sectioned and processed for histopathological examination. Results The modular lens was stable in all six rabbits. Uveal biocompatibility was similar to or better in the test eyes when compared with control eyes up to 6 weeks postoperatively. Overall, capsular bag opacification was found to be significantly lower in the test eyes when compared with control eyes. At the 6‐week gross examination, central posterior capsule opacification was scored as 0.58 ± 0.73 in the test group, and as 3.00 ± 1.26 in the control group (paired two samples for means t‐test; two‐tail P = 0.005). Conclusions The Harmoni Modular system remains stable within the capsular bag after implantation. Due to the design of the base component featuring long loops, along with peripheral anterior and posterior square edges, the lens appeared to prevent overall capsular bag opacification in the rabbit model.